Bowel Preparation before Elective Surgery - Kumar, Anjali S.; Kelleher, Deirdre C.; Sigle, Gavin W. (Clinics in Colon and Rectal Surgery, 2013)
Mechanical bowel preps were initially thought to decrease the bacterial load of the colon and therefore decrease infection. Traditional bowel preps include osmotic, laxative, and combination regimen. Data demonstrate that mechanical bowel preps are generally equivalent; however, the addition of oral antibiotics may further reduce the risk of infection. Recent data suggest that mechanical bowel preparations may not be necessary, and that dietary restrictions before surgery may also be obsolete. In this review, the authors address the types of mechanical bowel preparations (MBPs), differences in outcomes between MBPs, the role of oral antibiosis and enemas, the benefits of no MBP, and dietary preparations for elective colon and rectal surgery.
Keywords: mechanical bowel preparation; elective colorectal resection; oral antibiosis